Rancang Bangun Alat Pelindung Proses Intubasi - Zulhamidi, Zulhamidi; Armen, Armen (Politeknik ATI Padang, 2020)
Medical treatment of patients during the Covid-19 pandemic is a problem for medical staff related to the high risk of transmission. Medical staff (NAKES) need to be equipped with hight protective equipment to ensure they are not directly exposed from the patients whose status is unclear, whether infected or not. The most important equipment is protective equipment at the time of intubation that is useful to protect the doctor from sprinkling the patient's saliva. This study aims to redesign the intubation trachel instrument by the Department of Anesthesiology Uttaradit Hospital, Thailand by considering aspects of ergonomics and material limitations in Indonesia, especially in the city of Padang. The study was conducted using anthropometric data of Agro Industrial Engineering students. The results of this study are finding a trachel intubation tool that is simpler and more ergonomic without reducing its function as a personal protective device.